Towards the Study of Professional Corporate Education in Terms of Its Thematic Focus and Outcomes - Marta Matulčíková; Daniela Breveníková; Zuzana Geršicová; Jana Hanuliaková (Emerging Science Journal, 2024)
Aim: The aim of the paper is to characterize how the time for training employees in individual thematic areas is related to the outcomes and changes, facilitated by individual educational activities. Methods: The questionnaire method and interviewing methods were applied for obtaining data from respondents. The starting-point of empirical research was the knowledge and needs of the company, which perceives education as an investment. The respondent sample included 370 lectors/instructors and managers from three countries. The research was conducted in selected companies of section C âˆ’ Manufacturing, Statistical Classification of Economic Activities. Basic variables include the number of training hours and results of the changes after training activities. Three groups of employee education are analysed: general training, performance-oriented training and digital training. Findings: Our division of educational activities into three groups enables the fulfilment of the basic European Commission targets for the 2021âˆ’2027 programme. Recommendations: Invest in developing new skills through future corporate training in the context of innovative transformation of the economy for a smarter Europe. Create conditions for better utilisation of human potential by eliminating the discrepancy between offered and required skills. Novelty of the paper:international comparison of educational activities, focus on the smart Europe and transformation to Industry 4.0. Doi: 10.28991/ESJ-2024-SIED1-04 Full Text: PDF